THE EFFECT OF DUOLINGO ON THE STUDENTS’ TRANSLATION MASTERY AT THE VIII GRADE OF MTS PANCA DHARMA PADANGSIDIMPUAN - Lubis, Fitri Anjelina (jurnalalfa, 2023)
This study aims to determine whether students' translation skills can have a good effect using the Duolingo application for class VIII students using quantitative and qualitative methods. This research was conducted on 15 students of class VIII MTs Panca Dharma Padang Sidempuan. The results of this study indicate that the use of the Duolingo application is effective. This is evidenced by the data collected in the field. At that time the results of the pre-test were still bad. Then at the post-test stage 100% achieved the minimum completeness criteria. Therefore, related to the results of observations showed that students experienced an increase. Based on the students who passed the KKM above, it means that the actions taken were successful. The suggestion of this research to other researchers is to use the Duolingo application to help students' translation skills.